Can golden mussel shell be an alternative to limestone in soil correction? - Boni, Thaís Soto [UNESP]; Maltoni, Kátia Luciene [UNESP]; de Souza, Loiane Fernanda Romão [UNESP]; Cassiolato, Ana Maria Rodrigues [UNESP] (FapUNIFESP (SciELO), 2023)
Golden mussel is an invasive species in South America that causes environmental and economic damage due to the formation of large colonies without natural predators. This study aimed to test the agricultural use of golden mussel shell as a limestone substitute, as the shell is rich in calcium carbonate. The experiment was carried out in pots, with eight treatments (sandy soil; clay soil; sandy soil + 1.0 Mg ha-1 of limestone; clay soil + 1.0 Mg ha-1 of limestone; sandy soil + 1.0 Mg ha-1 of fresh shell; clay soil + 1.0 Mg ha-1 of fresh shell; sandy soil + 1.0 Mg ha-1 of calcined shell; clay soil + 1.0 Mg ha-1 of calcined shell), in addition to the application of the following fresh and calcined shell doses: 0, 1.0, 1.5 and 2.0 Mg ha-1. Rice was cultivated in all treatments, and the soil fertility and rice shoot and root dry masses were evaluated. The shell provided good chemical conditions to the soils and raised their pH and phosphorus and calcium contents. The agricultural use of golden mussel shell showed to be efficient for soil correction and can be considered an alternative to limestone.
Carapaça de mexilhão-dourado pode ser uma alternativa ao calcário na correção de solo?
Keywords: calcium carbonate; environmental residues; Limnoperna fortunei; soil acidity; soil amendment